2022
DOI: 10.5658/wood.2022.50.6.448
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Biofilm Formation in Yersinia enterocolitica by Edible Plant Extracts Including Polygoni Multiflori Radix

Abstract: Yersinia enterocolitica, which causes yersiniosis, is a bacterium that produces biofilms effectively. The inhibition of biofilm formation provides a method for preventing infections with Y. enterocolitica. In this study, the inhibitory activity of Y. enterocolitica biofilm formation was investigated in a library of 140 edible plant methanol extracts including forest products. It was identified that the biofilm formation could be inhibited by 12 extracts of plants

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Former studies have suggested that low concentrations of cinnamaldehyde (0.078 mg/mL) can repress the production of Y. enterocolitica biofilm [ 16 ]. In a previous study, it was shown that extracts from 12 edible plants inhibited the biofilm production of Y. enterocolitica [ 44 ]. Natural antibacterial agents cause abnormal expression of a few important genes, including luxS , glgC , envZ , ompF , kdpD , and cydB , resulting in the damage of the biofilm [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Former studies have suggested that low concentrations of cinnamaldehyde (0.078 mg/mL) can repress the production of Y. enterocolitica biofilm [ 16 ]. In a previous study, it was shown that extracts from 12 edible plants inhibited the biofilm production of Y. enterocolitica [ 44 ]. Natural antibacterial agents cause abnormal expression of a few important genes, including luxS , glgC , envZ , ompF , kdpD , and cydB , resulting in the damage of the biofilm [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have also reported the potential biological activity of extracts soluble in various polar solvents (i.e. methanol, ethanol, and distilled water) from several species such as Azadirachta excelsa seeds and Guibourtia tessmanii bark for anti-termite (Adfa et al, 2023;Ella Nkogo et al, 2022), herbal plants of Phellodendri cortex, Magnoliae cortex and some plants for antifungi (Na and Kim, 2022;Yoon and Kim, 2023), 12 herbal plants for antimicrobial resistance (Ham and Kim, 2022), Quercus gilva and Citrus × natsudaidai for antioxidant activity (Huh et al, 2022;Yang et al, 2022a) and the Lauraceae family for anti-asthmatic activity (Yang et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%